Esthetic rehabilitation of anterior teeth with molar-incisor hypomineralization and dental fluorosis: A case report - Cavalheiro, Jéssica Patrícia [UNESP]; De Souza, Mônica Irma Aparecida Valdeci [UNESP]; De Oliveira Duque, Carla Caroline; Bussaneli, Diego Girotto [UNESP]; Zuanon, Ângela Cristina Cilense [UNESP]; Jeremias, Fabiano [UNESP] (My University, 2020)
This case report describes the treatment of a patient who had molar-incisor hypomineralization associated with dental fluorosis, a diagnosis established through a comprehensive review of the clinical record, an intraoral clinical examination, and assessment of photographic records. First, dental hypersensitivity was treated with fluoride varnish, which was applied separately to each dental quadrant. Subsequently, the functional and esthetic reconstruction of the permanent maxillary central incisors was completed in a single session through the placement of direct composite resin veneers. After the treatment, the patient was reexamined monthly for 12 months to evaluate the durability of the restorations. At the 12-month follow-up, no fractures or pigmentations were observed, and only a slight loss of brightness of the restorations was noted. The dental hypersensitivity had been eliminated. When an adhesive restorative technique with composite resin is well executed, it is possible to obtain satisfactory and long-lasting esthetics and relief of painful symptoms.
Keywords: Composite resin veneers; Dental fluorosis; Esthetics; Molar-incisor hypomineralization; Oral health